IMPROVING LEARNING OUTCOMES THROUGH TEAM ASSISTED INDIVIDUALIZATION (TAI) COOPERATIVE LEARNING MODELS - Rusdi, Muhammad; admin, admin (Teaching English as a Foreign Language Overseas Journal, 2022)
The use of the Team Assisted Individualization (TAI) cooperative learning model can improve learning outcomes in students at SMA Muhammadiyah 5 Makassar. Classroom action research consisting of two cycles, where each cycle consists of two meetings, with activity stages including planning, implementing, observing, and reflecting. The subjects of this study were all fourth grade students at SMA Muhammadiyah 5 Makassar, Makassar, a total of 41 students consisting of 21 male students and 20 female students. The increase in learning outcomes through the Team Assisted Individualization (TAI) type cooperative learning model in students of SMA Muhammadiyah 5 Makassar is seen by the increasing average value of student learning outcomes in cycle I which is in the low category and is in the high category in cycle II. The results showed that the application of the Team Assisted Individualization (TAI) cooperative learning model could improve the learning outcomes of students at SMA Muhammadiyah 5 Makassar .